Spontaneous cerebrospinal fluid otorrhea – Case report and literature revision - Costa, Eurico (2011)
The authors present the case report of a 66 years old female patient, referred to our department at Hospital Prof. Doutor Fernando Fonseca for tinnitus and hearing loss, bilateral, more intense on the right side, with several years of evolution but worse in the last two years. Physical examination and audiometric tests were suggestive of otitis media with effusion.Nasal cavity and nasopharynx were normal. She underwent myringotomy for transtympanic ventilation tube placement. Immediately after myringotomy abundant drainage of a clear, colorless liquid was found, quickly filling the external auditory canal. A fluid sample was collected for biochemical analysis, including β2-transferrin, and the external auditory canal was packed. The result was consistent with cerebrospinal fluid. A computed tomography and magnetic resonance imaging were performed and a defect on the right temporal bone tegmen was found, without signs of meningoencephalocele.We proposed surgical repair of the defect.